Reduced graphene oxide (rGO) based wideband optical sensor and the role of Temperature, Defect States and Quantum Efficiency - Abid; Sehrawat, Poonam; Islam, S. S.; Mishra, Prabhash; Ahmad, Shahab (Scientific reports, 2018)
We report a facile and cost-effective approach to develop self-standing reduced Graphene Oxide (rGO) film based optical sensor and its low-temperature performance analysis where midgap defect states play a key role in tuning the crucial sensor parameters. Graphite oxide (GO) is produced by modified Hummers’ method and reduced thermally at 250 °C for 1 h in Argon atmosphere to obtain rGO. Self-standing rGO film is prepared via vacuum filtration. The developed film is characterized by HRTEM, FESEM, Raman, and XRD techniques. The developed sensor exhibits highest sensitivity towards 635 nm illumination wavelength, irrespective of the operating temperature. For a given excitation wavelength, photoresponse study at low temperature (123K–303K) reveals inverse relationship between sensitivity and operating temperature. Highest sensitivity of 49.2% is obtained at 123 K for 635 nm laser at power density of 1.4 mW/mm 2 . Unlike sensitivity, response- and recovery-time demonstrate directly proportional dependence with operating temperature. Power dependent studies establish linear relation between power-density and sensitivity, and a safe limit beyond which sample heating prolongs the recovery time. Wavelength-dependent studies shows that proposed sensor can efficiently operate from visible to near NIR region. To the best of our knowledge such rGO based optical sensor performance at low temperature had not been reported earlier.